Does Suicidal Ideation Influence Memory? A Study of the Role of Violent Daydreaming in the Relationship Between Suicidal Ideation and Everyday Memory. (September 2016) - Chu, Carol; Podlogar, Matthew C.; Rogers, Megan L.; Buchman-Schmitt, Jennifer M.; Negley, Jacob H.; Joiner, Thomas E.
Individuals at risk for suicide experience periods of emotional, enduring, and vivid thoughts about their death by suicide and frequently report violent daydreams about death. Daydreaming is associated with forgetfulness and memory impairments. However, no studies have examined whether suicidal ideation is associated with deficits in everyday memory capabilities and whether violent daydreaming may influence these relationships. This study tested these hypotheses in a sample of 512 young adults. Self-report measures of subjective everyday memory capabilities, violent daydreaming, and suicidal ideation were administered. Results indicated that suicidal ideation and violent daydreaming were each significantly associated with greater impairments in everyday memory retrieval and everyday memory encoding (i.e., attentional tracking). Furthermore, violent daydreaming accounted for the relationship between suicidal ideation and impairments in everyday memory retrieval and memory encoding. Notably, findings remained after controlling for gender and depressive symptoms, a robust predictor of memory impairments. Implications and limitations are discussed.